Ecophysiology and Growth of White Spruce Seedlings from Various Seed Sources along a Climatic Gradient Support the Need for Assisted Migration - Otis Prud'homme, Guillaume; Lamhamedi, Mohammed S.; Benomar, Lahcen; Rainville, André; DeBlois, Josianne; Bousquet, Jean; Beaulieu, Jean (Frontiers in Plant Science, 2018)
With climate change, favorable growing conditions for tree species are shifting northwards and to higher altitudes. Therefore, local populations are becoming less adapted to their environment. Assisted migration is one of the proposed adaptive measures to reduce the vulnerability of natural populations and maintain forest productivity. It consists of moving genetic material to a territory where future climate conditions correspond to those of its current location. Eight white spruce (Picea glauca [Moench] Voss) seed sources representing as many seed orchards were planted in 2013 at three forest sites simulating a south-north climatic gradient of 1.7°C in Québec, Canada. The objectives were to (1) evaluate the morpho-physiological responses of the different seed sources and (2) determine the role of genetic adaptation and physiological plasticity on the observed variation in morpho-physiological traits. Various seedling characteristics were measured, notably height growth from nursery to the fourth year on plantation. Other traits such as biomass and carbon allocation, nutritional status, and various photosynthetic traits before bud break, were evaluated during the fourth growing season. No interaction between sites and seed sources was observed for any traits, suggesting similar plasticity between seed sources. There was no change in the rank of seed sources and sites between years for height growth. Moreover, a significant positive correlation was observed between the height from the nursery and that after 4 years in the plantation. Southern seed sources showed the best height growth, while optimum growth was observed at the central site. Juvenile height growth seems to be a good indicator of the juvenile carbon sequestration and could serve as a selection criterion for the best genetics sources for carbon sequestration. Vector analysis showed no nitrogen deficiency 4 years after planting. Neither seed sources nor planting sites had a significant effect on photosynthesis before bud break. The observed results during the establishment phase under different site conditions indicate that southern seed sources may already benefit from assisted migration to cooler climatic conditions further north. While northern seed sources are likely to benefit from anticipated local global warming, they would not match the growth performance of seedlings from southern sources.